Religion, Race, and the American Presidency - Rozell, Mark J. (A journal of church and state, 2009)
This volume is a collection of research papers presented at an academic conference on religion, race, and the U.S. presidency. It includes contributions by a number of leading and emerging scholars primarily in the field of religion and politics. Several chapters focus on the relationship between leading faith traditions and the U.S. presidency: evangelicals, Mainline Protestants, Catholics, Jews, and Muslims. Others focus on race: African Americans, Latinos, and Asians. One chapter covers gender, another is on seculars., A standard criticism of edited books is a lack of comprehensiveness, especially the failure to cover certain important topics.